1998
DOI: 10.1093/clinchem/44.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 6-thioguanine and methyl 6-mercaptopurine nucleotides of azathioprine in red blood cells by HPLC

Abstract: 6-thioguanine (6-TGN) and methyl 6-mercaptopurine nucleotides (Me6-MPNs) are the two major metabolites found in erythrocytes after administration of azathioprine. In an attempt to understand the role of these metabolites in the pharmacologic and toxic activity of thiopurines, we have developed a HPLC method for the simultaneous determination of 6-TGNs and Me6-MPNs in erythrocytes. A simple and rapid treatment procedure based on deproteinization by perchloric acid with dithiothreitol is described. The nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(90 citation statements)
references
References 8 publications
1
83
0
6
Order By: Relevance
“…Second, despite the results of a large meta‐analysis which pointed out that the optimal dose to enhance the chance of achieving clinical response to AZA was the weighted full dose of 2.5 mg/kg, a poor correlation between the weight‐adjusted oral dose and serum 6TGN levels has been documented 5, 42, 43 . Finally, the optimal method to measure 6TGN RBC levels still remains an unresolved question 13, 44–46 ; moreover, some authors have suggested that there should be some other metabolites that could be more useful in predicting poor response to thiopurines 47 …”
Section: Discussionmentioning
confidence: 99%
“…Second, despite the results of a large meta‐analysis which pointed out that the optimal dose to enhance the chance of achieving clinical response to AZA was the weighted full dose of 2.5 mg/kg, a poor correlation between the weight‐adjusted oral dose and serum 6TGN levels has been documented 5, 42, 43 . Finally, the optimal method to measure 6TGN RBC levels still remains an unresolved question 13, 44–46 ; moreover, some authors have suggested that there should be some other metabolites that could be more useful in predicting poor response to thiopurines 47 …”
Section: Discussionmentioning
confidence: 99%
“…In all centres, tioguanine metabolites were determined in red blood cells (RBC) using a method by Dervieux and Boulieu . Due to a lack of standardised operating procedures for measuring thiopurine metabolites, we considered that analysed 6‐TGN concentrations might differ between the three hospital laboratories .…”
Section: Methodsmentioning
confidence: 99%
“…In patients on thiopurines treatment, analysis of thiopurine metabolites was carried out. The simultaneous determination in erythrocytes of 6‐tioguanine nucleotides (6‐TGN) and 6‐methylmercaptopurine (6‐MMP) was performed by the HPLC assay described elsewhere 30 with minor modifications. Plasma was decanted and the leucocytes and the upper layer of erythrocytes were removed.…”
Section: Methodsmentioning
confidence: 99%